Assessing the feasibility of the Virtual Reality Education and Acceptance Protocol among baseball and softball players - Jarad A. Lewellen; Cami A. Barnes; Aidan Forget; Jeanette M. Garcia; D. Jake Follmer; Guy Hornsby; Hannah L. Silva-Breen; Peter R. Giacobbi (PLoS ONE, 2025)
Research has supported the use of virtual reality (VR) in sport to train skills such as decision-making and anticipation, as well as aid in injury rehabilitation. Despite this, VR is not commonly used as a training tool in sport. Barriers to its adoption include a lack of understanding, low awareness, risk of cybersickness, and cost. As such, there is a critical need to address these barriers and promote acceptance of VR in sport. The purpose of this single-arm, non-randomized, mixed-methods feasibility trial was to examine the feasibility of the Virtual Reality Education and Acceptance Protocol (VREAP), which was designed by the study’s authors to address barriers to VR adoption. While the VREAP is intended to be used in multiple domains, we assessed its feasibility among baseball and softball players. Specifically, we assessed pre- and post-training attitudes toward VR using the Attitudes toward Virtual Reality Technology Scale (AVRTS), which uses the Technology Acceptance Model (TAM) as a guiding framework. Participants ( n = 18) completed the VREAP, which includes stages of education, acclimation, and application. Exit interviews provided further insights into participant experiences. Results from quantitative and reflexive content analyses demonstrated feasibility of the VREAP based on recruitment and adherence, acceptability, demand, implementation, and practicality. Statistical analyses from the AVRTS revealed significant pre- to post-training increases in overall attitudes toward VR as well as increases in enjoyment, perceived usefulness, and ease of use. Minimal cybersickness was reported. Our findings demonstrate the feasibility of the VREAP among baseball and softball players and show promise for its future research and application.